PENGARUH SOCIAL MEDIA MARKETING, BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING PADA J.CO DONUTS & COFFEE SEMARANG - Meatry Kurniasari; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2018)
The purpose of this study is to determine the influence of social media marketing and brand awareness of purchasing decisions through buying interest as an intervening variable J.CO Donuts & Coffee in Semarang City. This type of research is explanatory research. Sampling technique using non probability sampling technique with purposive sampling and Accidental sampling method. The number of samples taken as many as 100 respondents with a ratio of 40:60 in both branches J.CO Donuts & Coffee Semarang. In this study assisted by SPSS 16.0 system. The results showed that social media marketing influence on buying interest by contributing 15.6% while the rest influenced by factors other than social media marketing. Brand Awareness influences buying interest by contributing 31.3% while the rest is influenced by factors other than brand awareness. Meanwhile, buying interest influences the purchasing decision by contributing 23.3% while the rest is influenced by factors other than buying interest. Based on result of regression analysis of two stages known that variable of buying interest can be intervening variable from social media marketing and brand awareness to purchasing decision. It means that the better social media marketing and brand awareness, the higher the buying interest and the better the buying interest, the higher the purchasing decision of J.CO Donuts & Coffee in Semarang City.